Assessment, endoscopy, and treatment in patients with acute severe ulcerative colitis during the COVID-19 pandemic (PROTECT-ASUC): a multicentre, observational, case-control study. (April 2021) - Sebastian, Shaji; Walker, Gareth J; Kennedy, Nicholas A; Conley, Thomas E; Patel, Kamal V; Subramanian, Sreedhar; Kent, Alexandra J; Segal, Jonathan P; Brookes, Matthew J; Bhala, Neeraj; Gonzalez, Haidee A; Hicks, Lucy C; et al.
Summary: Background: There is a paucity of evidence to support safe and effective management of patients with acute severe ulcerative colitis during the COVID-19 pandemic. We sought to identify alterations to established conventional evidence-based management of acute severe ulcerative colitis during the early COVID-19 pandemic, the effect on outcomes, and any associations with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and severe COVID-19 outcomes. Methods: The PROTECT-ASUC study was a multicentre, observational, case-control study in 60 acute secondary care hospitals throughout the UK. We included adults (≥18 years) with either ulcerative colitis or inflammatory bowel disease unclassified, who presented with acute severe ulcerative colitis and fulfilled the Truelove and Witts criteria. Cases and controls were identified as either admitted or managed in emergency ambulatory care settings between March 1, 2020, and June 30, 2020 (COVID-19 pandemic period cohort), or between Jan 1, 2019, and June 30, 2019 (historical control cohort), respectively. The primary outcome was the proportion of patients with acute severe ulcerative colitis receiving rescue therapy (including primary induction) or colectomy. The study is registered with ClinicalTrials.gov, NCT04411784 . Findings: We included 782 patients (398 in the pandemic period cohort and 384 in the historical control cohort) who met the Truelove and Witts criteria for acute severe ulcerative colitis. The proportion of patients receiving rescue therapy (including primary induction) or surgery was higher during the pandemic period than in the historical period (217 [55%] of 393 patients vs 159 [42%] of 380 patients; p=0·00024) and the time to rescue therapy was shorter in the pandemic cohort than in the historical cohort (p=0·0026). This difference was driven by a greater use of rescue and primary induction therapies with biologicals, ciclosporin, or tofacitinib in the COVID-19 pandemic period cohort than in the historical control period cohort (177 [46%] of 387 patients in the COVID-19 cohort vs 134 [36%] of 373 patients in the historical cohort; p=0·0064). During the pandemic, more patients received ambulatory (outpatient) intravenous steroids (51 [13%] of 385 patients vs 19 [5%] of 360 patients; p=0·00023). Fewer patients received thiopurines (29 [7%] of 398 patients vs 46 [12%] of 384; p=0·029) and 5-aminosalicylic acids (67 [17%] of 398 patients vs 98 [26%] of 384; p=0·0037) during the pandemic than in the historical control period. Colectomy rates were similar between the pandemic and historical control groups (64 [16%] of 389 vs 50 [13%] of 375; p=0·26); however, laparoscopic surgery was less frequently performed during the pandemic period (34 [53%] of 64] vs 38 [76%] of 50; p=0·018). Five (2%) of 253 patients tested positive for SARS-CoV-2 during hospital treatment. Two (2%) of 103 patients re-tested for SARS-CoV-2 during the 3-month follow-up were positive 5 days and 12 days, respectively, after discharge from index admission. Both recovered without serious outcomes. Interpretation: The COVID-19 pandemic altered practice patterns of gastroenterologists and colorectal surgeons in the management of acute severe ulcerative colitis but was associated with similar outcomes to a historical cohort. Despite continued use of high-dose corticosteroids and biologicals, the incidence of COVID-19 within 3 months was low and not associated with adverse COVID-19 outcomes. Funding: None.